Assessment of the genetic diversity of a critically endangered species Centaurea amaena (Asteraceae) - Atasagun, Bayram (Archives of Biological Sciences, 2022)
Paper description: This study was conducted to investigate the level of genetic diversity within and between two amaena populations. Prospective outcomes are expected to provide essential information for establishing effective conservation strategies for critically threatened C. amaena. ISSR markers were used to detect the level of genetic diversity in amaena populations. A total of 50 ISSR primers were used and 13 primers producing polymorphic and reproducible products were selected. A high level of genetic diversity was detected both at population and species levels. Habitat conservation is the preferred strategy to preserve the genetic diversity of amaena in this region. Abstract: Centaurea amaena is an endemic and endangered species listed as CR (critically endangered) in Turkey. ISSR markers were used to detect the level of genetic diversity in two natural populations of C. amaena. A total of 50 ISSR primers were used and 13 primers producing polymorphic and reproducible products were selected. These primers yielded 102 amplified discernible loci, of which 80 (78%) were polymorphic. A high level of genetic diversity was detected both at population and species levels; the effective number of alleles (Ne) was 1.544, the observed number of alleles (Na) was 1.784, the Nei’s genetic diversity (H) was 0.306, and Shannon's information index was 0.447. The established gene flow (Nm) was 2.329, indicating a high migration rate between the populations. A moderate level of genetic differentiation (GST: 0.176) was also observed. Analysis of molecular variance (AMOVA) revealed that 24.89% of the total genetic diversity resided among populations, while 75.10% was within the populations. Cluster analysis showed that samples from the same locality clustered together and there was no cross-clustering between the samples. The patterns of genetic variation indicate that existing C. amaena populations should be conserved.